Tectonic implications of a myionitic granite in the lower structural levels of the Tierra Caliente complex (Guerrero terrane), southern Mexico - Mariano Elías-Herrera; José Luis Sánchez-Zavala (Revista Mexicana de Ciencias Geológicas)
Two sequences of pre-Tertiary volcano-sedimentary rocks with island arc affinities have been differentiated in the Zacazonapan area, State of Mexico. These rocks are part of the Tierra Caliente complex or the tectonostratigraphic Guerrero terrane.